Prevalence and Factors Associated with Acute Chest Syndrome among Children with Sickle Cell Anaemia in Kitgum General Hospital, Uganda - Omara, Peter; Ladu, Adama Isah; Laker, Joan; Apio, Shiella Gloria (International Journal of Health Sciences, 2025)
Purpose: This study aimed to identify the prevalence and factors associated with acute chest syndrome among children with sickle cell anaemia in Kitgum General Hospital, Kitgum district, northern Uganda. Methodology: A retrospective study among children admitted with sickle cell anemia was conducted. Data review was conducted for hospital admissions from January 2020 to December 2022 at the paediatrics unit of Kitgum General Hospital. A summary table (data collection table) was developed in Microsoft Excel sheets. Data collection was done over 4-weeks period to extract secondary data for children aged six (6) months to 17 years admitted with sickle cell anaemia from the month of January 2020 to December 2022. Acute chest syndrome was defined as a respiratory sickness in sickle cell anemia patients that presented with fever and/or symptoms of cough, difficult/fast breathing, and low oxygen concentration of the blood requiring hospitalisation. Data was analysed using software Statistical Package for Social Sciences (SPSS) Version 28.0 (190). Associated factors were measured according to p-values where any ‘p’ value less than 0.05 was considered statistically significant. Findings: Two hundred seventy (n=270) participants were included in the study with the median age (IQR-25% to 75%) of 8.0 years (4.0 – 11.0). There were more males, 57.4% (n=155) than female 42.6%, (n=115). The prevalence of acute chest syndrome was 27.8% (CI 22.0% – 33.0%). Age was found to be a statistically significant factor, (p=0.001). Unique Contribution to Theory, Policy and Practice: The prevalence of acute chest syndrome among children with sickle cell anaemia was identified as 27.8% with 95% confidence that the true prevalence value lies between 22.0% to 33.0%. There is need for total integration of sickle cell disease care into the routine primary healthcare services instead of the one-day a week clinic.